Vertical Distribution of Moisture in a Growing Sweet Corn Canopy During MicroWEX-4 - Joaquin Casanova; Jasmeet Judge; Mi-young Jang (EDIS)
Circular 1492, a 9-page illustrated report by Joaquin Casanova, Jasmeet Judge, and Mi-young Jang, describes the methods and measurements of the canopy moisture distribution in sweet corn during a growing season. Published by the UF Department of Agricultural and Biological Engineering, August 2006.